Effects of information-based regulation on financial outcomes: Evidence from the European Union's public emission registry - Dietrich Earnhart; Robert Germeshausen; Kathrine von Graevenitz (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Information-based policies play an important role in environmental protection efforts around the world. These policies use information provision and/or disclosure to shape behavior in order to meet the policy objective; for example, mandatory information disclosure requires firms to measure and report their pollutant emissions. This study investigates the influence of a particular information-based policy - the European Union's mandatory and public emission registry of polluting facilities - on financial outcomes of German firms: revenues, costs, and profits. Using detailed firm-level data for the years 1998 to 2016, we exploit size- and pollution-specific reporting thresholds to isolate the effect of this policy. We compare firms that own facilities required to report in the first EPER wave with similar firms that do not own such facilities. For this comparison, we deploy both a difference-in-differences design and an event study. Our findings suggest that the introduction of EPER in 2001 increased both operating revenues and expenditures, yielding a neutral impact on the operating profits of affected firms. These results support neither of the two competing hypotheses regarding financial outcomes: costly regulation hypothesis and Porter Hypothesis.
Keywords: K32; L21; O31; Q52; Q58; 330; Information-based Regulation; Environmental Policy; Financial Performance; Porter Hypothesis